Política e religião: o envolvimento dos católicos carismáticos na política brasileira - Reis, Marcos Vinicius de Freitas (2011)
The objective of this study is to analyze the political behavior of politicians linked to the Catholic Charismatic Renewal (CCR). The choice of politicians with such religious affiliation was given due to the significant number of adherents, the Catholic Church's support and the national visibility for its events . For this, bills of state and federal deputies have been analysed, to know if their proposals are consistent with their political parties and CCR s interests. The study drew a biographical profile of heir representatives and the reasons that led charismatic Catholics to step into the political arena.